2022
DOI: 10.1007/s12144-022-03030-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychology as a historical science? Theoretical assumptions, methodological considerations, and potential pitfalls

Abstract: The current condition of (Western) academic psychology can be criticized for various reasons. In the past years, many debates have been centered around the so-called “replication crisis” and the “WEIRD people problem”. However, one aspect which has received relatively little attention is the fact that psychological research is typically limited to currently living individuals, while the psychology of the past remains unexplored. We find that more research in the field of historical psychology is required to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…From the 1980s until today, Jüttemann has invested a lot of effort into promoting his vision of historical psychology and the psychogenesis of humankind. Although the general idea that psychology should show more interest in the historicity of the human psyche has been reemphasized in recent publications (Hutmacher & Mayrhofer, 2021, 2022; Muthukrishna et al, 2021), Jüttemann’s own pioneer work has largely been ignored by mainstream psychology. The present paper has tried to understand the reasons for this, in order to draw conclusions for the future of historical psychology.…”
Section: Conclusion: the Future Of Historical Psychologymentioning
confidence: 99%
See 3 more Smart Citations
“…From the 1980s until today, Jüttemann has invested a lot of effort into promoting his vision of historical psychology and the psychogenesis of humankind. Although the general idea that psychology should show more interest in the historicity of the human psyche has been reemphasized in recent publications (Hutmacher & Mayrhofer, 2021, 2022; Muthukrishna et al, 2021), Jüttemann’s own pioneer work has largely been ignored by mainstream psychology. The present paper has tried to understand the reasons for this, in order to draw conclusions for the future of historical psychology.…”
Section: Conclusion: the Future Of Historical Psychologymentioning
confidence: 99%
“…In addition, realizing that the human psyche has changed and evolved over time might provide an interesting and inspiring starting point to rethink the structures of our societies: if cross-temporal variability exists, this also means that the current state of things is neither unchangeable nor unavoidable (see also Graeber & Wengrow, 2021). Although these basic ideas have been renewed in recent publications (Hutmacher & Mayrhofer, 2021, 2022; Muthukrishna et al, 2021), they have already been described by various authors over several decades (e.g., Barbu, 1960; Danziger, 2003; Gergen, 1973; Jüttemann, 1986a; Meyerson, 1987; Smith, 2005; van den Berg, 1961).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneously, others argue that psychology is experiencing a—as we term it— universality crisis : Over the course of the years, it has been demonstrated that even very basic processes of thinking (Nisbett, 2003), feeling (Osgood et al, 1975), and perception (Segall et al, 1966) show considerable cross-cultural variation. Furthermore, typical psychological samples are severely limited regarding their cultural diversity (Apicella et al, 2020; Henrich et al, 2010) and their sensitivity to cross-temporal variation (Hutmacher, 2022; Hutmacher & Mayrhofer, 2021, 2023; Muthukrishna et al, 2021), which makes the scope of psychological findings unclear. A third crisis diagnosis is brought forward by those who claim that psychology faces a theory crisis (Eronen & Bringmann, 2021; Oberauer & Lewandowsky, 2019) in the sense that many psychological theories are ill-developed and underspecified microtheories (for an early critique, see Meehl, 1978).…”
mentioning
confidence: 99%